Climate feedbacks in DICE-2013R: Modeling and empirical results - Heiko Wirths; Joachim Rathmann; Peter Michaelis (Universität Augsburg, Institut für Volkswirtschaftslehre, 2016)
Climate feedback mechanisms that have the potential to intensify global warming have been omitted almost completely in the integrated assessment of climate change and the economy so far. With the present paper we try to narrow this gap in literature. We discuss different types of feedback mechanisms and show how to incorporate them into the mathematical setup of the well-known integrated assessment model DICE-2013R. Subsequently, we choose the permafrost carbon feedback (PCF) as specific application for an empirical analysis. We calibrate the parameters for our modified version of the DICE-2013R model and compute the optimal emission mitigation rates that maximize welfare accounting for the impact of the PCF. Finally, we quantify the economic losses resulting from a mitigation policy which ignores this feedback mechanism. Our empirical results generally indicate that accounting for the PCF leads to an increase in the optimal mitigation rates.
urn:nbn:de:bvb:384-opus4-710895
Keywords: O44; Q54; Q58; 330; integrated assessment; DICE model; climate feedbacks; permafrost